Association between the risk of heart failure hospitalization and end-stage renal disease with digoxin usage in patients with cardiorenal syndrome: A population-based study - Chang, Kai-Ting; Kuo, Hsuan-Fu; Chang, Yu-Han; Wang, Yu-Tsang; Yang, Lii-Jia; Niu, Sheng-Wen; Kuo, I-Ching; Chen, Yumay; Wen, Zhi-Hong; Hung, Chi-Chih; Chang, Jer-Ming; Lin, Hugo Y.-H (Frontiers in Public Health, 2023)
Background The management of the coexistence of heart disease and kidney disease is increasingly challenging for clinicians. Chronic kidney disease (CKD) is not only a prevalent comorbidity of patients with heart failure but has also been identified as a noteworthy risk factor for all-cause mortality and poor clinical outcomes. Digoxin is one of the commonest treatments for heart disease. There are few trials investigating the role of digoxin in patients with cardiorenal syndrome (CRS). This study aims to examine the association between digoxin usage and clinical outcomes in patients with CRS in a nationwide cohort. Method We conducted a population-based study that included 705 digoxin users with CRS; each patient was age, sex, comorbidities, and medications matched with three non-users who were randomly selected from the CRS population. Cox proportional hazards regression analysis was conducted to estimate the effects of digoxin on the incidence of all-cause mortality, congestive heart failure (CHF) hospitalization, coronary artery disease (CAD) hospitalization, and end-stage renal disease (ESRD). Results The all-cause mortality rate was significantly higher in digoxin users than in non-users (adjusted hazard ratio [aHR] = 1.26; 95% confidence interval [CI] = 1.09–1.46, p = 0.002). In a subgroup analysis, there was significantly high mortality in the 0.26–0.75 defined daily dose (DDD) subgroup of digoxin users (aHR = 1.49; 95% CI = 1.23–1.82, p<0.001). Thus, the p for trend was 0.013. With digoxin prescription, the CHF hospitalization was significantly higher [subdistribution HR (sHR) = 1.17; 95% CI = 1.05–1.30, p = 0.004], especially in the >0.75 DDD subgroup (sHR = 1.19; 95% CI = 1.01–1.41, p = 0.046; p for trend = 0.006). The digoxin usage lowered the coronary artery disease (CAD) hospitalization in the > 0.75 DDD subgroup (sHR = 0.79; 95% CI = 0.63–0.99, p = 0.048). In renal function progression, more patients with CRS entered ESRD with digoxin usage (sHR = 1.34; 95% CI = 1.16–1.54, p<0.001). There was a significantly greater incidence of ESRD in the < 0.26 DDD and 0.26–0.75 DDD subgroups of digoxin users (sHR = 1.32; 95% CI = 1.06–1.66, p = 0.015; sHR = 1.44; 95% CI = 1.18–1.75; p for trend<0.001). Conclusion Digoxin should be prescribed with caution to patients with CRS.